n-type material for thermoelectric conversion, method for manufacturing the same, doping solution, and thermoelectric conversion element
Patent Information
- Application Number
- JP2025030483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2026-09-08
AI Technical Summary
【0010】 本開示によれば、耐久性に優れる熱電変換素子を形成可能な熱電変換用n型材料が提供される。また、本開示によれば、当該熱電変換用n型材料を容易に製造可能な製造方法、当該熱電変換用n型材料を形成するためのドープ液、及び、当該熱電変換用n型材料を含有する熱電変換素子が提供される。
Smart Images

Figure 2026143079000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an n-type material for thermoelectric conversion, a method for producing the same, a doping solution, and a thermoelectric conversion element.
Background Art
[0002] Thermoelectric conversion is a technology that directly converts heat into electricity using the Seebeck effect, and has attracted attention as an energy recovery technology that converts waste heat generated when using fossil fuels into electricity.
[0003] The thermoelectric conversion element used in the above field is preferably a bipolar element including both a material exhibiting p-type conductivity and a material exhibiting n-type conductivity, but many nanomaterials exhibit p-type conductivity. Therefore, there is a demand for a technique for converting a nanomaterial exhibiting p-type conductivity into a nanomaterial exhibiting n-type conductivity.
[0004] For example, Patent Document 1 discloses an n-type dopant that converts a nanomaterial exhibiting p-type conductivity into a nanomaterial exhibiting n-type conductivity.
[0005] Whether a nanomaterial exhibits p-type conductivity or n-type conductivity can be determined by the sign of the Seebeck coefficient (when the Seebeck coefficient is positive, the nanomaterial exhibits p-type conductivity, and when the Seebeck coefficient is negative, the nanomaterial exhibits n-type conductivity).
Prior Art Literature
Patent Literature
[0006]
Patent Document 1
Summary of the Invention
Problem to be Solved by the Invention
[0007] However, conventional thermoelectric conversion elements using n-type materials have durability issues, such as the possibility of a rapid decrease in output in high-temperature, high-humidity environments even when sealed.
[0008] This disclosure aims to provide an n-type thermoelectric material capable of forming a thermoelectric element with excellent durability. Furthermore, this disclosure aims to provide a manufacturing method for easily producing the n-type thermoelectric material, a doping solution for forming the n-type thermoelectric material, and a thermoelectric element containing the n-type thermoelectric material. [Means for solving the problem]
[0009] This disclosure provides, for example, the following [1] to
[20] . [1] A thermoelectric n-type material obtained by doping a dopant into a p-type thermoelectric material containing carbon nanotubes, The dopant contains an alkali metal cation and a crown ether having a 1-octanol / water partition coefficient of 1 or more, wherein the material is an n-type material for thermoelectric conversion. [2] A thermoelectric n-type material obtained by doping a dopant into a p-type thermoelectric material containing carbon nanotubes, An n-type thermoelectric material comprising the dopant containing an alkali metal cation and a crown ether having two or more aromatic rings. [3] The n-type thermoelectric material according to [1] or [2], wherein the 1-octanol / water partition coefficient of the crown ether is 1.3 or greater. [4] The n-type thermoelectric material according to any one of [1] to [3], wherein the crown ether has two or more aromatic rings that share two carbon atoms with the crown ether ring. [5] The n-type thermoelectric material according to any one of [1] to [4], wherein the crown ether has two or more benzene rings that share two carbon atoms with the crown ether ring. [6] The n-type thermoelectric material according to any one of [1] to [5], wherein the crown ether is a crown ether having a total number of atoms constituting the crown ether ring of 9 to 33. [7] The n-type thermoelectric material according to any one of [1] to [6], wherein the dopant further contains an anion that is a complex ion. [8] The n-type thermoelectric material according to [7], wherein the anion is a complex ion containing an iron atom. [9] The thermoelectric conversion n-type material according to any one of [1] to [8], wherein the aforementioned thermoelectric conversion n-type material further contains a conductive resin.
[10] The n-type thermoelectric material according to [9], wherein the conductive resin comprises poly(3,4-ethylenedioxythiophene) and an electron acceptor.
[11] A doping solution for converting a p-type thermoelectric material containing carbon nanotubes into an n-type thermoelectric material, wherein the doping solution comprises: A doping solution comprising, as the dopant, an alkali metal cation and a crown ether having a 1-octanol / water partition coefficient of 1 or more.
[12] A doping solution for converting a p-type thermoelectric material containing carbon nanotubes into an n-type thermoelectric material by doping it with a dopant, A doping solution comprising, as the dopant, an alkali metal cation and a crown ether having two or more aromatic rings.
[13] The doping solution according to
[11] or
[12] , comprising a first liquid containing the alkali metal cation and a second liquid containing the crown ether.
[14] A method for manufacturing an n-type material for thermoelectric conversion described in any one of [1] to
[10] , A method for producing an n-type thermoelectric material, comprising the step of doping a p-type thermoelectric material containing carbon nanotubes with the dopant.
[15] The step described above comprises: a first step of impregnating the p-type material for thermoelectric conversion with a first liquid containing the alkali metal cation; a second step of impregnating the p-type material for thermoelectric conversion with a second liquid containing the crown ether; The method for producing an n-type material for thermoelectric conversion according to
[14] , comprising the steps above.
[16] The method for producing an n-type material for thermoelectric conversion according to
[15] , wherein the second step is performed after the first step.
[17] The method for producing an n-type material for thermoelectric conversion according to
[15] , wherein the first step is performed after the second step.
[18] The method for producing an n-type material for thermoelectric conversion according to any one of
[14] to
[17] , wherein the step is a step of doping a part of a resin layer containing the p-type material for thermoelectric conversion with the dopant to obtain a thermoelectric conversion layer containing the p-type material for thermoelectric conversion and the n-type material for thermoelectric conversion.
[19] A thermoelectric conversion element comprising the n-type material for thermoelectric conversion according to any one of [1] to
[10] .
[20] A thermoelectric conversion element comprising a thermoelectric conversion layer containing a p-type material for thermoelectric conversion containing carbon nanotubes and the n-type material for thermoelectric conversion according to any one of [1] to
[10] .
Effects of the Invention
[0010] According to the present disclosure, an n-type material for thermoelectric conversion capable of forming a thermoelectric conversion element excellent in durability is provided. Further, according to the present disclosure, there are provided a production method capable of easily producing the n-type material for thermoelectric conversion, a doping solution for forming the n-type material for thermoelectric conversion, and a thermoelectric conversion element containing the n-type material for thermoelectric conversion.
Brief Description of Drawings
[0011] [Figure 1] It is a figure showing the evaluation results of long-term reliability in Examples 1 to 3 and Comparative Example 1. [Modes for carrying out the invention]
[0012] Preferred embodiments of this disclosure are described in detail below. <n-type material for thermoelectric conversion> The n-type thermoelectric material of this embodiment is obtained by doping a p-type thermoelectric material with a dopant. The dopant contains an alkali metal cation and a crown ether. The crown ether is a crown ether with a 1-octanol / water partition coefficient of 1 or more, or a crown ether having two or more aromatic rings.
[0013] According to the inventors' findings, in conventional n-type materials, under high temperature and high humidity conditions, the dopant is hydrated by water entering the system, and the dopant hydrate diffuses into the p-type material, causing a portion of the p-type material to become n-type, resulting in a significant decrease in the output of the thermoelectric conversion element. In contrast, in the thermoelectric conversion n-type material of this embodiment, by using a specific crown ether as the dopant, the hydration and diffusion of the dopant are suppressed, thereby suppressing the decrease in the output of the thermoelectric conversion element.
[0014] In a preferred embodiment, the crown ether is a crown ether with a 1-octanol / water partition coefficient of 1 or greater. A 1-octanol / water partition coefficient of 1 or greater means that the affinity for 1-octanol is higher than the affinity for water. Such a crown ether is less likely to be hydrated even if water enters the system. Therefore, such a crown ether suppresses the decrease in output of the thermoelectric conversion element due to dopant diffusion.
[0015] In this embodiment, the 1-octanol / water partition coefficient is the value measured by the method described in "Partition coefficients of crown ethers, Recueil des Travaux Chimiques des Pays-Bas, 108, (1989) 103-108".
[0016] In another preferred embodiment, the crown ether is a crown ether having two or more aromatic rings. Such a crown ether has improved hydrophobicity due to the presence of aromatic rings, and the 1-octanol / water partition coefficient tends to be 1 or greater. Furthermore, such a crown ether has excellent affinity for carbon nanotubes because it has multiple aromatic rings that interact with carbon nanotubes, and therefore does not easily hydrate with water that enters the system. For this reason, with such a crown ether, even if the 1-octanol / water partition coefficient is less than 1, the decrease in output of the thermoelectric conversion element due to dopant diffusion is sufficiently suppressed.
[0017] In yet another preferred embodiment, the crown ether may be a crown ether having a 1-octanol / water partition coefficient of 1 or more and having two or more aromatic rings. With such a crown ether, hydration with water that has entered the system is suppressed by the mechanism of action described above, and the decrease in output of the thermoelectric conversion element due to dopant diffusion is significantly suppressed.
[0018] (Thermoelectric conversion p-type material) The p-type material for thermoelectric conversion contains carbon nanotubes.
[0019] Carbon nanotubes may be single-layered, double-layered, or multi-layered, but single-layered is preferred from the viewpoint of further improving the electrical conductivity of the thermoelectric conversion material (p-type material for thermoelectric conversion and n-type material for thermoelectric conversion described later).
[0020] The carbon nanotubes preferably include single-walled carbon nanotubes. The proportion of single-walled carbon nanotubes to the total amount of carbon nanotubes may be, for example, 25% by mass or more, and from the viewpoint of further improving the electrical conductivity of the thermoelectric conversion material, it may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 95% by mass or more, or even 100% by mass.
[0021] The diameter of the single-walled carbon nanotube is not particularly limited and may be, for example, 20 nm or less, 10 nm or less, 5 nm or less, or 3 nm or less. Furthermore, the diameter of the single-walled carbon nanotube may be, for example, 0.4 nm or more, or 0.5 nm or more.
[0022] In this specification, the diameter of single-walled carbon nanotubes is defined as 100-300 cm² by Raman spectroscopy. -1 The wavenumber of the peak that appears (ω(cm) -1 From this, the diameter (nm) can be calculated using the formula: diameter (nm) = 248 / ω.
[0023] As a method for evaluating single-walled carbon nanotubes, the G / D ratio in laser Raman spectroscopy is known. The G / D ratio of single-walled carbon nanotubes in laser Raman spectroscopy at a wavelength of 532 nm may be, for example, 10 or more, or 20 or more. Using such single-walled carbon nanotubes tends to yield thermoelectric conversion materials with even better electrical conductivity. The upper limit of the above G / D ratio is not particularly limited and may be, for example, 500 or less, or 300 or less.
[0024] The carbon nanotube content may be, for example, 20% by mass or more, 30% by mass or more, 40% by mass or more, or 50% by mass or more, based on the total amount of the p-type material for thermoelectric conversion. Alternatively, the carbon nanotube content may be, for example, 100% by mass or less, 99% by mass or less, 95% by mass or less, or 90% by mass or less, based on the total amount of the p-type material for thermoelectric conversion.
[0025] The p-type material for thermoelectric conversion may further contain a conductive resin.
[0026] The conductive resin is not particularly limited, and any known conductive resin used in p-type materials for thermoelectric conversion can be used without any particular restriction. Examples of conductive resins include polyaniline-based conductive polymers, polythiophene-based conductive polymers, polypyrrole-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, and polyphenylene-vinylene-based conductive polymers. Poly(3,4-ethylenedioxythiophene) can be used as an example of a polythiophene-based conductive polymer.
[0027] The conductive resin may be, for example, a conductive resin composed of poly(3,4-ethylenedioxythiophene) (hereinafter sometimes referred to as PEDOT) and an electron acceptor. Such a conductive resin tends to have a higher electrical conductivity than the thermoelectric conversion material.
[0028] Examples of electron acceptors include polystyrene sulfonic acid, polyvinyl sulfonic acid, poly(meth)acrylic acid, polyvinyl sulfonic acid, toluene sulfonic acid, dodecylbenzene sulfonic acid, camphor sulfonic acid, bis(2-ethylhexyl) sulfosuccinate, chlorine, bromine, iodine, phosphorus pentafluoride, arsenic pentafluoride, boron trifluoride, hydrogen chloride, sulfuric acid, nitric acid, tetrafluoroboric acid, perchloric acid, iron(III) chloride, and tetracyanoquinodimethane. From the viewpoint of further improving the electrical conductivity of the thermoelectric conversion material, the electron acceptor may be, for example, polystyrene sulfonic acid (hereinafter sometimes referred to as PSS).
[0029] (Dopant) In this specification, a dopant is defined as a substance that alters the Seebeck coefficient of the material to which the dopant is applied.
[0030] In this specification, "changing the Seebeck coefficient" means decreasing the value of the Seebeck coefficient or changing the value of the Seebeck coefficient from a positive value to a negative value. Thermoelectric materials exhibiting a positive Seebeck coefficient have p-type conductivity, and thermoelectric materials exhibiting a negative Seebeck coefficient have n-type conductivity. The Seebeck coefficient can be measured, for example, by the measurement method described in the examples later, and the polarity of the thermoelectric material can be determined from the positive or negative value of the measured value.
[0031] The dopant contains an alkali metal cation and a crown ether. The dopant may also further contain an anion.
[0032] In this embodiment, it is believed that the crown ether contained in the dopant captures a cation, causing the anion to dissociate. This anion then changes the carriers of the carbon nanotube from holes to electrons, thereby converting the p-type material to an n-type material.
[0033] Examples of alkali metal cations include sodium ions, potassium ions, and lithium ions.
[0034] The anion may be, for example, a complex ion. Because complex ions have a larger ion size, they dissociate well with cations captured by the crown ether, and therefore the effect of n-type conversion is thought to be more pronounced. In addition, because complex ions have a metal atom at the center of the anion, it is thought that the interaction between this metal atom and the carbon nanotube promotes n-type conversion more significantly.
[0035] Furthermore, when the anion is a complex ion, metal atoms derived from the complex ion remain in the n-type material for thermoelectric conversion. These metal atoms function as antioxidants, suppressing changes in the physical properties of the n-type material over time and improving storage stability.
[0036] The complex ion may be an anion selected from the group consisting of, for example, ferrocyanide ions, ferricyanide ions, tetrachloroferrate(III) ions, tetrachloroferrate(II) ions, tetracyanonickelate(II) ions, tetrachloronickelate(II) ions, tetracyanocobalt(II) ions, tetrachlorocobalt(II) ions, tetracyanocopper(I) ions, tetrachlorocopper(II) ions, hexacyanochrome(III) ions, tetrahydroxyzinc(II) ions, and tetrahydroxyaluminin(III) ions.
[0037] The complex ion may contain, for example, iron atoms. When the complex ion contains iron atoms, the iron atoms remaining in the n-type thermoelectric material function suitably as antioxidants, further suppressing changes in the physical properties of the n-type thermoelectric material over time and improving storage stability.
[0038] The complex ion containing the iron atom may be an anion selected from the group consisting of, for example, ferrocyanide ions, ferricyanide ions, tetrachloroferrate(III) ions, and tetrachloroferrate(II) ions, or it may be a ferrocyanide ion. With such a complex ion, the iron atom functions more favorably as an antioxidant, and storage stability is further improved. Furthermore, with such a complex ion, the properties of n-type materials for thermoelectric conversion tend to be better.
[0039] When the complex ion contains iron atoms, the iron atom content in the n-type material for thermoelectric conversion may be, for example, 0.001% by mass or more, and from the viewpoint of obtaining the above-mentioned effects more significantly, it may be 0.005% by mass or more, or 0.01% by mass or more. Furthermore, the iron atom content in the n-type material for thermoelectric conversion may be, for example, 15% by mass or less, 12% by mass or less, or 10% by mass or less. In this specification, the iron atom content refers to the value measured by scanning electron microscopy (SEM)-energy-dispersive X-ray spectroscopy (EDS).
[0040] The anion may be, for example, an anion produced when the complex salt dissociates in the doping solution. The complex salt may be, for example, a salt of the alkali metal cation and the complex ion described above. Examples of complex salts include potassium ferrocyanide, sodium ferrocyanide, potassium ferricyanide, sodium ferricyanide, potassium tetrachloroferrate(III), sodium tetrachloroferrate(III), potassium tetrachloroferrate(II), sodium tetrachloroferrate(II), etc. The complex salt may also be a hydrate.
[0041] Crown ethers are macrocyclic ether compounds that have a crown ether ring. The total number of atoms constituting the crown ether ring may be, for example, 12 or more. Alternatively, the total number of atoms constituting the crown ether ring may be, for example, 33 or less, 30 or less, 27 or less, or 24 or less.
[0042] The 1-octanol / water partition coefficient of the crown ether may be, for example, 1 or greater, and from the viewpoint of obtaining the above-mentioned effects more significantly, it may be 1.3 or greater, 1.5 or greater, 1.7 or greater, 1.9 or greater, or 2.0 or greater. The 1-octanol / water partition coefficient of the crown ether may be, for example, 3.5 or less, and from the viewpoint of obtaining the above-mentioned effects more significantly, it may be 3.0 or less, 2.7 or less, or 2.3 or less.
[0043] A crown ether may be, for example, a crown ether having two or more aromatic rings. The number of aromatic rings in a crown ether may be, for example, 2 to 6, 2 to 4, or 2.
[0044] Examples of aromatic rings found in crown ethers include benzene rings, naphthalene rings, anthracene rings, phenanthrene rings, pyridine rings, quinoline rings, isoquinoline rings, indole rings, fluorene rings, and carbazole rings. From the viewpoint of obtaining more favorable interactions with carbon nanotubes, the aromatic ring found in crown ethers may be a benzene ring.
[0045] The aromatic ring in a crown ether may share two carbon atoms with the crown ether ring. Crown ethers having such an aromatic ring tend to exhibit a more pronounced hydration-inhibiting effect due to the presence of the aromatic ring in the vicinity of the crown ether ring.
[0046] The aromatic ring of the crown ether may be an unsubstituted aromatic ring or may have substituents. Examples of substituents include alkyl groups, nitro groups, amino groups, substituted amino groups (e.g., dialkylamino groups, diarylamino groups, etc.), halogeno groups (e.g., fluoro groups, chloro groups, bromo groups, iodo groups, etc.), alkoxy groups, hydroxyl groups, carboxyl groups, cyano groups, sulfo groups, aldehyde groups, aryl groups, thiol groups, amide groups, ureido groups, perfluoroalkyl groups (e.g., trifluoromethyl groups), acyl groups (e.g., acetyl groups), etc. The substituent may also be a group formed by bonding the aromatic ring of the crown ether to an alkyl group or aryl group with a divalent group (e.g., ether groups, thioether groups, carbonyl groups, ester groups, azo groups, amide groups, imide groups, urethane groups, urea groups, etc.).
[0047] Examples of crown ethers include dibenzo-9-crown-3-ether, dibenzo-12-crown-4-ether, dibenzo-15-crown-5-ether, dibenzo-18-crown-6-ether, dibenzo-21-crown-7-ether, dibenzo-24-crown-8-ether, dibenzo-27-crown-9-ether, dibenzo-30-crown-10-ether, dibenzo-33-crown-11-ether, tribenzo-18-crown-6-ether, tribenzo-21-crown-7-ether, tribenzo-24-crown-8-ether, tribenzo-30-crown-10-ether, tetrabenzo-24-crown-8-ether, tetrabenzo-32-crown-10-ether, naphthalene-crown-ether, and dinaphthalene-crown-ether.
[0048] The molar ratio (C2 / C1) of the amount of crown ether C2 to the amount of cation C1 may be, for example, 0.1 or more, 0.3 or more, or 0.5 or more. Furthermore, the molar ratio (C2 / C1) may be, for example, 5 or less, 3 or less, or 2 or less.
[0049] The dopant may be doped into the thermoelectric conversion p-type material by, for example, impregnating the thermoelectric conversion p-type material with a doping solution containing the dopant.
[0050] In this embodiment, cations (and anions) are water-soluble, while crown ethers have low water solubility. Therefore, in this embodiment, it is preferable to dop the p-type thermoelectric conversion material with a dopant using a two-component doping solution comprising a first solution containing cations (and anions) and a second solution containing crown ether. However, if a solvent capable of dissolving both cations (and anions) and crown ethers is used, the doping solution may be a one-component type.
[0051] The first solution may contain water as a solvent. The first solution may be, for example, an aqueous solution of a cation (and anion).
[0052] The cation concentration in the first solution may be, for example, 0.001 mol / L or higher, and from the viewpoint of reducing the number of doping applications, it may be 0.01 mol / L or higher, 0.05 mol / L or higher, or 0.1 mol / L or higher. Furthermore, the cation concentration in the first solution may be, for example, 3 mol / L or lower, and from the viewpoint of doping diffusion, it may be 2 mol / L or lower, 1.7 mol / L or lower, or 1.5 mol / L or lower.
[0053] The second solution may contain an organic solvent. The organic solvent can be any solvent capable of dissolving crown ether. Examples of organic solvents include dimethyl sulfoxide (DMSO), cyclohexane, acetonitrile, methanol, ethanol, 1-butanol, chloroform, tetrachloromethane, trichloromethane, ethyl acetate, dichloromethane, tetrahydrofuran, pyridine, acetone, nitromethane, ethyl acetate, toluene, benzene, and formic acid.
[0054] The concentration of crown ether in the second solution may be, for example, 0.0001 mol / L or higher, and from the viewpoint of reducing the number of doping applications, it may be 0.001 mol / L or higher, 0.01 mol / L or higher, or 0.1 mol / L or higher. Furthermore, the concentration of crown ether in the second solution may be, for example, 2 mol / L or less, and from the viewpoint of doping diffusion, it may be 1.5 mol / L or less, 1 mol / L or less, or 0.5 mol / L or less.
[0055] The order in which the first and second liquids are supplied to the p-type thermoelectric material is not particularly limited. For example, the first liquid may be supplied to the p-type thermoelectric material, dried, then the second liquid may be supplied and dried, or the second liquid may be supplied to the p-type thermoelectric material, dried, then the first liquid may be supplied and dried.
[0056] (Method for manufacturing n-type materials for thermoelectric conversion) The n-type material for thermoelectric conversion in this embodiment may be manufactured, for example, by the following manufacturing method.
[0057] The manufacturing method of this embodiment includes a step of doping the above-mentioned p-type thermoelectric conversion material with the above-mentioned dopant (hereinafter also referred to as the n-type conversion step).
[0058] The method of doping the p-type material for thermoelectric conversion with a dopant in the n-type conversion process is not particularly limited, and one example is to bring the p-type material for thermoelectric conversion into contact with a doping solution containing the dopant.
[0059] The n-type conversion process may include, for example, a first impregnation step of impregnating the p-type material for thermoelectric conversion with the first liquid, and a second impregnation step of impregnating the p-type material for thermoelectric conversion with the second liquid.
[0060] The order in which the first impregnation process and the second impregnation process are carried out is not particularly limited. For example, the second impregnation process may be carried out after the first impregnation process, or the first impregnation process may be carried out after the second impregnation process.
[0061] The n-type conversion step may further include a first solvent removal step, which removes the solvent from the material after the first liquid impregnation, following the first impregnation step. Alternatively, the n-type conversion step may further include a second solvent removal step, which removes the solvent from the material after the second liquid impregnation, following the second impregnation step.
[0062] In the first solvent removal step and the second solvent removal step, the method of removing the solvent is not particularly limited, and examples include methods of removing the solvent by heat treatment, reduced pressure treatment, etc.
[0063] In this embodiment, the portion of the p-type thermoelectric material that is doped with a dopant becomes the n-type thermoelectric material. In this embodiment, the entire p-type thermoelectric material may be doped with a dopant to form the n-type thermoelectric material, or a portion of the p-type thermoelectric material may be doped with a dopant to form a composite of the p-type thermoelectric material and the n-type thermoelectric material.
[0064] In one preferred embodiment, the n-type conversion step may be a step of doping a portion of a resin layer containing a p-type material for thermoelectric conversion with a dopant to obtain a thermoelectric conversion layer containing a p-type material and an n-type material for thermoelectric conversion. By such a step, a thermoelectric conversion layer containing a p-type material and an n-type material can be easily obtained. Furthermore, in such a step, by appropriately setting the range to which the dopant is applied, the p-type material and the n-type material can be placed at any desired position, thus easily obtaining a thermoelectric conversion layer having a desired p / n configuration.
[0065] Furthermore, in the above process, a thermoelectric conversion layer is formed in which the p-type material and the n-type material are adjacent to each other. Since such a thermoelectric conversion layer is configured to facilitate the diffusion of dopants in the n-type material into the p-type material, the effects described above, resulting from the adoption of the specific dopant in this embodiment, are more pronounced.
[0066] The shape of the n-type material for thermoelectric conversion is not particularly limited. For example, a film-like n-type material for thermoelectric conversion supported on a support can be obtained by doping a dopant onto a composite material in which a p-type material for thermoelectric conversion has been deposited on a support.
[0067] The film thickness of the n-type material for thermoelectric conversion may be, for example, 100 nm to 1 mm, 200 nm to 800 μm, or 300 nm to 600 μm, from the viewpoint of obtaining appropriate electrical resistance and excellent flexibility.
[0068] The n-type thermoelectric material of this embodiment can be suitably used as an n-type material for thermoelectric elements. Furthermore, the n-type thermoelectric material of this embodiment can also be suitably used in applications such as Peltier elements and temperature sensors.
[0069] <Thermoelectric conversion element> The thermoelectric conversion element of this embodiment includes the above-mentioned n-type material for thermoelectric conversion. The thermoelectric conversion element of this embodiment may further include the above-mentioned p-type material for thermoelectric conversion.
[0070] The thermoelectric conversion element may, for example, comprise two conductive substrates and a thermoelectric conversion layer disposed between the conductive substrates. The thermoelectric conversion layer may include the above-mentioned n-type thermoelectric conversion material and further include the above-mentioned p-type thermoelectric conversion material.
[0071] The two conductive substrates can also be referred to as the first electrode and the second electrode, respectively.
[0072] The thermoelectric element may be manufactured by a manufacturing method that includes a lamination step of arranging a thermoelectric layer containing an n-type thermoelectric material and a p-type thermoelectric material on a conductive substrate.
[0073] The thermoelectric element may also be manufactured by a manufacturing method that includes, for example, a lamination step of placing a resin layer containing a p-type thermoelectric material on a conductive substrate, and an n-type conversion step of doping a portion of the resin layer with a dopant to obtain a thermoelectric layer containing an n-type thermoelectric material and a p-type thermoelectric material.
[0074] The n-type conversion process may be the same as the n-type conversion process described above.
[0075] The thermoelectric element may further include configurations other than those described above. For example, the thermoelectric element may further include a sealant for sealing the thermoelectric layer, wiring for electrically connecting thermoelectric elements to each other or for drawing power to an external circuit, and an insulating material or thermally conductive material for controlling the thermal conductivity of the thermoelectric elements.
[0076] While preferred embodiments of this disclosure have been described above, this disclosure is not limited to the embodiments described above. [Examples]
[0077] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.
[0078] (Example 1) <Insulating materials> An insulating sheet (Sumitomo Riko Co., Ltd.'s "FineShlight (registered trademark) standard type," thickness: 0.63 mm, silica aerogel, thermal conductivity: 0.02 W / mK, coefficient of linear expansion: 136 ppm / K) was cut to a width of 10 mm and a length of 96 mm to be used as an insulating material.
[0079] <Dispersion> 80 g of a carbon nanotube dispersion (concentration: 0.2 mass%, G / D ratio: 41, aqueous dispersion, single-walled carbon nanotubes, diameter 0.9-1.7 nm, thermal conductivity 30 W / mK) was concentrated by vacuum until the carbon nanotube concentration reached 0.4 mass%. Subsequently, 5.7 g of a PEDOT / PSS aqueous dispersion (Heraeus K.K. "Clevious PH1000", solid content concentration: 1.2 mass%) and the concentrated carbon nanotube dispersion were thoroughly stirred using a three-one motor (AS ONE Corporation "PM203" model) (stirring time: 30 minutes). This prepared a dispersion with a carbon nanotube content of 50 mass% relative to the total amount of PEDOT / PSS and carbon nanotubes. Shear rate 0.01 s -1 The viscosity of the dispersion was 1,320,000 mPa·sec. The viscosity of the dispersion was measured using a rheometer (Anton Paar "MCR302" (product name)). The measurement conditions were: temperature: 25°C, plate: φ25 mm parallel plate, gap: 1 mm.
[0080] <Dopant Solution> A first solution with a potassium ion concentration of 0.1 M was prepared by dissolving 0.16 g of potassium ferrocyanide trihydrate in 15 mL of ultrapure water. A second solution with a concentration of 0.48 M was prepared by dissolving 0.26 g of dibenzo-18-crown-6-ether in 15 mL of dimethyl sulfoxide. Insoluble matter in the first and second solutions was removed using a membrane filter with a pore size of 0.45 μm (DISMIC25HP045AN).
[0081] <Circuit board> The substrate is a 100mm x 35mm polyethylene naphthalate film (manufactured by Toyobo Co., Ltd., film thickness 25μm, water vapor transmission rate 6.0g / m²). 2 A polyethylene naphthalate film with a radiation emissivity of 0.93, thermal conductivity of 0.33 W / mK, and flexural modulus of 2.3 GPa was prepared. The above polyethylene naphthalate film was washed with acetone and used as a substrate.
[0082] <Sealing layer> A 100mm x 35mm polyethylene naphthalate film was prepared as the sealing layer. The polyethylene naphthalate film was washed with acetone, and adhesive tape (Nitto Denko No. 585, with an acrylic adhesive layer) was applied to one of its main surfaces.
[0083] <Manufacturing of thermoelectric conversion modules> The dispersion was applied to the first main surface of the substrate using a Musashi Engineering jet dispenser "AeroJet" and a desktop robot "SHOTMASTER400ΩX". Subsequently, the laminate coated with the dispersion was placed in a forced-air dryer set to 60°C for 3 hours. This formed a composite film with a thickness of 21 μm on the first main surface of the substrate. The composite film provided both a thermoelectric conversion region and a conductive region on the first main surface of the substrate. The direction in which the thermoelectric conversion region extends is perpendicular to the direction in which the heat conduction portion and the heat insulating member extend. A high-precision digital micrometer (Mitutoyo Corporation, MDH-25MB) was used to measure the thickness of the composite film. Specifically, the thickness of the portion where the composite film is provided and the thickness of the portion where the composite film is not provided (the portion with only the substrate) were measured, and the difference between the two was taken as the thickness of the composite film. Next, the first main surface of the substrate was immersed in DMSO (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) at room temperature for 30 minutes. Subsequently, the substrate removed from the DMSO was placed on a hot plate set to 60°C for 120 minutes. This formed a p-type thermoelectric conversion layer on the first main surface of the substrate. In Example 1, the thickness of the p-type thermoelectric conversion layer was 5.0 μm.
[0084] Next, the first liquid was dropped onto a portion of the p-type thermoelectric conversion layer that functions as a thermoelectric conversion element using a Fujifilm inkjet printer, the "Material Printer DMP2850". In Example 1, the first liquid was first dropped onto an area 2 mm wide along the first direction and 5.5 mm long along the second direction. Subsequently, the first liquid was dropped again onto an area 2 mm wide and 5.5 mm long, with a gap of 5.5 mm along the first direction. By repeating this dropping operation, areas where the first liquid was dropped and areas where it was not dropped were arranged alternately. Next, the substrate was dried for 30 minutes, the second solution was applied in the same manner as the first solution, and the substrate was dried for 60 minutes. Subsequently, the substrate was placed in a forced-air dryer set to 100°C for 60 minutes. Based on the above, 24 p-type thermoelectric elements and 24 n-type thermoelectric elements were formed on the substrate. In other words, a total of 48 thermoelectric elements were formed on the substrate. Thus, a total of 24 thermoelectric conversion sections were formed, each containing one p-type thermoelectric element and one n-type thermoelectric element. Here, the thickness of the n-type thermoelectric elements was substantially the same as the thickness of the p-type thermoelectric elements. The edges of each thermoelectric conversion section overlapped with the heat conduction section, and at least the center of each thermoelectric conversion section did not overlap with the heat conduction section. The iron atom content in the n-type thermoelectric elements was between 0.01% by mass and 10% by mass.
[0085] Next, the adhesive tape side of the sealing layer was pressed onto the first main surface of the substrate on which the p-type and n-type thermoelectric elements were formed. The substrate was placed in the chamber of a manual hydraulic vacuum heating press (Imoto Seisakusho Co., Ltd., IMC-11FD model), the plate temperature was set to 80°C, and vacuuming was performed for 1 minute. The press was then applied at a pressure of 1kN for more than 10 minutes. As a result, a laminate was obtained in which the thermoelectric elements were sandwiched between the substrate and the sealing layer.
[0086] Next, spray adhesive (3M Japan Limited, Regular Series S / N 55) was applied to one side of the above-mentioned heat insulating material, and it was attached to the second main surface of the substrate with a gap of 1.0 mm. Next, a high thermal conductivity material (Shin-Etsu Chemical Co., Ltd., G-789) was applied to the gap using an Iwashita Engineering dispenser "AD3000C" and a desktop robot "EzROBO-5GX". At this time, the spacing along the first direction from which the high thermal conductivity material was discharged was set to 11 mm, and the application was carried out while moving the nozzle along a second direction perpendicular to the first direction. As a result, multiple strip-shaped high thermal conductivity materials were applied to the second main surface. After application, the substrate was placed on a hot plate set to 120°C for 60 minutes. This formed multiple heat-conducting parts (coefficient of linear expansion: 140 ppm / K, thermal conductivity: 3.0 W / mK). The length T2 of the heat conduction section 5 was 1 mm, the width L2 of the heat conduction section was 1 mm, and the distance S between the heat conduction sections in the first direction was 10 mm. In addition, an insulating material (coefficient of linear expansion: 136 ppm / K, thermal conductivity: 0.02 W / mK) was placed and fixed to fill the 10 mm gap. Based on the above, the thermoelectric conversion module of Example 1 was manufactured.
[0087] (Example 2) A thermoelectric conversion module was manufactured in the same manner as in Example 1, except that the crown ether dissolved in the second solution was changed to dibenzo-21-crown-7-ether.
[0088] (Example 3) A thermoelectric conversion module was manufactured in the same manner as in Example 1, except that the crown ether dissolved in the second solution was changed to dibenzo-24-crown-8-ether.
[0089] (Comparative Example 1) The thermoelectric conversion module was manufactured in the same manner as in Example 1, except that the two liquids were not separated into a first liquid and a second liquid, and benzo-18-crown-6-ether was added to the first liquid.
[0090] (Evaluation of thermoelectric conversion modules) The thermoelectric conversion modules of Examples 1-3 and Comparative Example 1 were evaluated using the following method.
[0091] <Output Measurement> The heat conduction section of the thermoelectric conversion module was brought into contact with a 100°C hot plate to create a temperature difference within each thermoelectric conversion element, and the maximum output of the thermoelectric conversion module was measured using a source meter (Tektronix "Keithley 2612B").
[0092] <Evaluation of long-term reliability> The thermoelectric conversion module was left standing in an environment of 85°C and 85% humidity. After a predetermined period of time, it was removed, and the maximum output of the thermoelectric conversion module was measured using the method described above. The results are shown in Figure 1.
[0093] As shown in Figure 1, the thermoelectric conversion module of Comparative Example 1 maintained a high output until 100 hours had elapsed, but the output decreased significantly after 200 hours. In contrast, the thermoelectric conversion modules of Examples 1 to 3 maintained a stable and good output from the start of the long-term reliability test until 1000 hours had elapsed.
Claims
1. A thermoelectric n-type material obtained by doping a dopant into a p-type thermoelectric material containing carbon nanotubes, The dopant contains an alkali metal cation and a crown ether having a 1-octanol / water partition coefficient of 1 or more, wherein the material is an n-type material for thermoelectric conversion.
2. A thermoelectric n-type material obtained by doping a dopant into a p-type thermoelectric material containing carbon nanotubes, The dopant comprises an alkali metal cation and a crown ether having two or more aromatic rings, wherein the material is an n-type thermoelectric material.
3. The n-type thermoelectric material according to claim 1 or 2, wherein the 1-octanol / water partition coefficient of the crown ether is 1.3 or more.
4. The n-type thermoelectric material according to claim 1 or 2, wherein the crown ether has two or more aromatic rings that share two carbon atoms with the crown ether ring.
5. The n-type thermoelectric material according to claim 1 or 2, wherein the crown ether has two or more benzene rings that share two carbon atoms with the crown ether ring.
6. The n-type thermoelectric material according to claim 1 or 2, wherein the crown ether is a crown ether having a total number of atoms constituting the crown ether ring of 9 to 33.
7. The n-type thermoelectric material according to claim 1 or 2, wherein the dopant further contains an anion that is a complex ion.
8. The n-type thermoelectric material according to claim 7, wherein the anion is a complex ion containing an iron atom.
9. The thermoelectric conversion n-type material according to claim 1 or 2, wherein the aforementioned thermoelectric conversion n-type material further contains a conductive resin.
10. The n-type thermoelectric material according to claim 9, wherein the conductive resin is composed of poly(3,4-ethylenedioxythiophene) and an electron acceptor.
11. A doping solution for converting a p-type thermoelectric material containing carbon nanotubes into an n-type thermoelectric material by doping it with a dopant, The dopant comprises an alkali metal cation and a crown ether having a 1-octanol / water partition coefficient of 1 or more.
12. A doping solution for converting a p-type thermoelectric material containing carbon nanotubes into an n-type thermoelectric material by doping it with a dopant, A doping solution comprising, as the dopant, an alkali metal cation and a crown ether having two or more aromatic rings.
13. The doping solution according to claim 11 or 12, comprising a first liquid containing the alkali metal cation and a second liquid containing the crown ether, in a two-component type.
14. A method for manufacturing an n-type material for thermoelectric conversion according to claim 1 or 2, A method for producing an n-type thermoelectric material, comprising the step of doping a p-type thermoelectric material containing carbon nanotubes with the dopant.
15. The above process is, The first step involves impregnating the p-type thermoelectric material with the first liquid containing the alkali metal cation, A second step involves impregnating the p-type thermoelectric material with a second liquid containing the crown ether, A method for producing an n-type thermoelectric material according to claim 14, including the method described in claim 14.
16. A method for manufacturing an n-type material for thermoelectric conversion according to claim 15, wherein the second step is performed after the first step.
17. A method for manufacturing an n-type material for thermoelectric conversion according to claim 15, wherein the first step is performed after the second step.
18. The method for manufacturing an n-type thermoelectric material according to claim 14, wherein the step is to dope a portion of the resin layer containing the p-type thermoelectric material with the dopant to obtain a thermoelectric layer containing the p-type thermoelectric material and the n-type thermoelectric material.
19. A thermoelectric element comprising the n-type material for thermoelectric conversion described in claim 1 or 2.
20. A thermoelectric element comprising a thermoelectric conversion layer containing a p-type thermoelectric conversion material containing carbon nanotubes and an n-type thermoelectric conversion material according to claim 1 or 2.
Citation Information
Patent Citations
Nanomaterial dopant composition composite, dopant composition, and method for manufacturing nanomaterial dopant composition composite
WO2015198980A1